Web navigation for individuals with dyslexia: an exploratory study - Al-Wabil, Areej; Zaphiris, Panayiotis; Wilson, Stephanie (My University, 2007)
In this paper, we present an exploratory study of the web navigation experiences of dyslexic users. Findings indicate that dyslexics exhibit distinctive web navigation behaviour and preferences. We believe that the outcomes of this study add to our understanding of the particular needs of this web user population and have implications for the design of effective navigation structures.